Evaluation of Serum Kallistatin Levels in Women with Preeclampsia and its Role in Assessing Preeclampsia Severity - Rangeen Badri Mahdi; Esraa Hameed Al-Maini (Mustansiriya Medical Journal, 2024)
Background: Preeclampsia (PE) is a hypertension condition that often manifests after 20 weeks of gestation. It is regarded as a leading cause of death among mothers and babies globally. Aim: To evaluate how serum kallistatin affects PE severity. Patients and Methods: A case–control study that included three groups of 95 third trimester pregnant women with viable fetuses was chosen. Group M (32 mild PE), Group S (31 severe PE), and Group C (32 control pregnant normotensives). Serum kallistatin, complete blood count, liver, and renal functions were compared between groups, at An Al-Yarmouk Teaching Hospital Obstetrics and Gynecology. Results: The concentrations of serum kallistatin in severe PE were markedly lower than those in mild and normotensive pregnant women. (1.79, 3.24, and 4.55, P < 0.001). Kallistatin accurately predicted mild, severe, and normotensive PE. All healthy women’s parameters did not correlate with kallistatin. In PE, age, gestational age, and platelets correlated directly with kallistatin, but systolic and diastolic blood pressure, alanine transaminase, aspartate aminotransferase, and total serum bilirubin correlated inversely. Kallistatin had higher sensitivity than specificity and comparable negative to positive predictive values. Conclusions: Mother’s serum kallistatin is inversely related to PE severity and significantly lower in PE patients than normotensives. Kallistatin’s sensitivity and specificity for predicting PE in normotensive women were 93.7% and 68.8%, respectively, using a threshold value ≤3.92 ng/ml using a threshold value ≤2.136 ng/ml, 90.3%, and 93.8% predicted severe PE from mild PE, respectively.